Correction: Helical orbitals and circular currents in linear carbon wires. Issue 9 (24th February 2020) - Garner, Marc H.; Jensen, Anders; Hyllested, Louise O. H.; Solomon, Gemma C.
Abstract : Correction for 'Helical orbitals and circular currents in linear carbon wires' by Marc H. Garner et al., Chem. Sci., 2019, 10, 4598–4608.